The Effect of Sex on Disease Stage and Survival after Radical Cystectomy in Non-Urothelial Variant-Histology Bladder Cancer - Flammia, Rocco Simone; Tufano, Antonio; Chierigo, Francesco; Würnschimmel, Christoph; Hoeh, Benedikt; Sorce, Gabriele; Tian, Zhen; Anceschi, Umberto; Leonardo, Costantino; Del Giudice, Francesco; Terrone, Carlo; Giordano, Antonio; et al. (Journal of clinical medicine, 2023)
BACKGROUND: Female sex in patients treated by radical cystectomy (RC) is associated with more advanced stage and worse survival. However, studies supporting these findings mostly or exclusively relied on urothelial carcinoma of the urinary bladder (UCUB) and did not address non-urothelial variant-histology bladder cancer (VH BCa). We hypothesized that female sex is associated with a more advanced stage and worse survival in VH BCa, similarly to that of UCUB. MATERIALS AND METHODS: Within the SEER database (2004-2016), we identified patients aged ≥18 years, with histologically confirmed VH BCa, and treated with comprehensive RC. Logistic regression addressing the non-organ-confined (NOC) stage, as well as cumulative incidence plots and competing risks regression addressing CSM for females vs. males, were fitted. All analyses were repeated in stage-specific and VH-specific subgroups. RESULTS: Overall, 1623 VH BCa patients treated with RC were identified. Of those, 38% were female. Adenocarcinoma (n = 331, 33%), neuroendocrine tumor (n = 304, 18%), and other VH (n = 317, 37%) were less frequent in females but not squamous cell carcinoma (n = 671, 51%). Across all VH subgroups, female patients had higher NOC rates than males did (68 vs. 58%, p < 0.001), and female sex was an independent predictor of NOC VH BCa (OR = 1.55, p = 0.0001). Overall, five-year cancer-specific mortality (CSM) were 43% for females vs. 34% for males (HR = 1.25, p = 0.02). CONCLUSION: In VH BC patients treated with comprehensive RC, female sex is associated with a more advanced stage. Independently of stage, female sex also predisposes to higher CSM.
Keywords: muscle-invasive bladder cancer; variant-histology; squamous cell carcinoma; adenocarcinoma; radical cystectomy; neuroendocrine carcinoma